The role and mechanism of fatty acid oxidation in cancer drug resistance - Yun Lei; Shuang Cai; Jia-Kui Zhang; Si-Qi Ding; Zhan-He Zhang; Chun-Dong Zhang; Dong-Qiu Dai; Yong-Shuang Li (Cell Death Discovery)
Abstract Cancer is a leading cause of death globally. While drug treatment is the most commonly used method for cancer therapy, it is often hampered by drug resistance. Consequently, the mechanisms of drug resistance in cancer therapy have become a focus of current research. The mechanisms underlying cancer drug resistance are complex and may involve genetic mutation, immune escape, and metabolic reprogramming, amongst others. Metabolic reprogramming is an important marker of tumor cells, and an increasing number of studies have shown that cancer drug resistance is correlated with metabolic reprogramming, especially when fatty acid oxidation (FAO) is involved. More importantly, many preclinical studies have shown that when anti-tumor drugs are combined with FAO inhibitors, cancer cell resistance to drugs can be reversed and the effectiveness of tumor therapy is enhanced. This review provides a comprehensive overview of the mechanisms by which FAO leads to cancer resistance as well as potential targets for inhibition of FAO.